Legal Counseling on Corruption Prevention in Village Fund Budget Management - Saimima, Judy Marria; Titahelu, Juanrico Alfaromona Sumaresz; Corputty, Patrick; Muammar, Muammar (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Corruption of village funds is still an astonishing phenomenon in the midst of the implementation of village government. It is even recorded that villages are one of the largest contributors to corruption cases in Indonesia today.Purposes of The Devotion: This service aims to provide education to the community, how important it is to prevent potential corruption of village funds and how to involve community participation in prevention. Method of The Devotion: This activity was carried out in the form of legal counseling in Waipirit Village, Kairatu District, West Seram through a panel discussion where the presenters delivered material in turn and then continued with questions and answers between the presenters and the community.Results Main Findings of the Devotion: Based on the legal counseling activities carried out, one of which is a discussion, it shows that many participants, especially from the community, initially consider corruption in the management of village funds as a trivial problem. However, after participating in the discussion, they became more aware of the negative impact of corruption and the serious legal consequences for the perpetrators.